The Effect of Physical Activity Zone 3 on The The Effect of Aerobic Heart Rate Zone Physical Activities on the Body's Systole Diastol System on the Students of FIK UNMRelax Heart Rate and Peak Flow Rate - Sulaeman Sulaeman; Hasyim Hasyim; Bakkareng Bakkareng; Etno Setyagraha (STKIP Muhammadiyah Kuningan, 2022)
This study aimed to determine the effect of aerobic heart rate zone physical activity on the systolic and diastolic systems. This type of research is quantitative with an experimental approach (Pretest-posttest one group design). The sample in this study amounted to 10 samples selected through the purposive sampling technique: data collection techniques using systolic and diastolic measurement tests. At the same time, the treatment given is in the form of aerobic heart rate zone physical activity. Hypothesis testing using paired T-test or influence test. The results of the hypothesis testing the effect of aerobic heart rate zone physical activity on systole obtained a significant value of 0.023, which is smaller than 0.05. Furthermore, the average value before treatment was 128.4000, and after treatment was 125.0000. So it can be concluded that aerobic heart rate zone physical activity has a significant effect on systole. The results of the hypothesis testing the impact of aerobic heart rate zone physical activity on diastole obtained a substantial value of 0.004, which is smaller than 0.05. Furthermore, the average value before treatment was 82,5000, and after treatment was 79.5000. So it can be concluded that aerobic heart rate zone physical activity has a significant effect on diastole.